2016
DOI: 10.1007/s13187-016-1022-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual Degrees in Medicine: Options for Medical Students

Abstract: Increasingly, more universities are showing an interest in offering combined degrees (most commonly research-based) with their medical degree. Intercalated degrees often require the medical student to take time off their medical course in order to pursue the second degree full-time. Concurrent degrees, on the other hand, do not usually require taking additional time to complete; rather, they are integrated into the medical curriculum. Exposing medical students to the array of opportunities offered by their aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Dual degrees include intercalated degrees, which require students to take time off to pursue the second degree full-time, and concurrent degrees, which are integrated into the medical curriculum (Alamri, 2018). Examples of dual degrees include MD/MBA programs (Ackerly et al, 2011;Patel et al, 2014) and combined MD/MPH degrees in topics such as public policy, law, biomedical engineering, arts, bioethics, public health and epidemiology (Alamri, 2018). The majority of graduates of joint medical degree programs reportedly enters the clinical workforce upon graduation (Brass et al, 2010;Jeffe & Andriole, 2011;Patel et al, 2014;Sullivan et al, 2017).…”
Section: Dual Degreesmentioning
confidence: 99%
“…Dual degrees include intercalated degrees, which require students to take time off to pursue the second degree full-time, and concurrent degrees, which are integrated into the medical curriculum (Alamri, 2018). Examples of dual degrees include MD/MBA programs (Ackerly et al, 2011;Patel et al, 2014) and combined MD/MPH degrees in topics such as public policy, law, biomedical engineering, arts, bioethics, public health and epidemiology (Alamri, 2018). The majority of graduates of joint medical degree programs reportedly enters the clinical workforce upon graduation (Brass et al, 2010;Jeffe & Andriole, 2011;Patel et al, 2014;Sullivan et al, 2017).…”
Section: Dual Degreesmentioning
confidence: 99%
“…For this review, we examined both intercalated and non-intercalated degree options because such options are an intrinsic part of some medical degree programmes. Intercalated degree options have been previously reported [12,13], but not in the context of what is available or undertaken by students who do not complete an intercalated programme. Jones et al's systematic review covered intercalated bachelor degrees (but not intercalated masters and PhDs).…”
Section: Introductionmentioning
confidence: 99%
“…The need for such qualified clinicians is paramount due to their unique position of seeing patients’ problems first-hand, while also collecting research data to inform better ways to solve those problems [2]. We have previously reviewed the available opportunities for medical students to undertake research, and found internationally that there are a multitude of opportunities afforded during their medical degree studies to complete research, either as core or elective [3].…”
Section: Introductionmentioning
confidence: 99%